Las neuronas espejo en el desarrollo de habilidades socioemocionales para fortalecer las conductas prosociales durante el aprendizaje colaborativo en alumnos de séptimo año de Educación General Básica de la Escuela Alejandro Sergio Bermeo de la Ciudad de Chimbo, Provincia de Bolívar, estudio realizado durante los meses de septiembre a diciembre del 2024. - Castillo Patiño, Melanni Tathiana (2025)
15 VI. ABSTRACT This study investigated the impact of mirror neurons on the development of socio- emotional skills to strengthen prosocial behaviors during collaborative learning among seventh- grade students of Basic General Education at the Alejandro Sergio Bermeo School in the city of Chimbo, Bolívar Province, the aim was to foster prosocial behaviors through the mediation of mirror neurons to develop socio-emotional skills in students, a mixed-methods approach with both qualitative and quantitative focus was employed, using expert interviews and data analysis, the results revealed diverse behaviors and attitudes in the classroom, with deficiencies in interpersonal relationships and emotional management, highlighting the need for timely teacher support, in conclusion, it was found that students' socio-emotional skills and prosocial behaviors were intermittent and at a medium level, therefore, a pedagogical intervention is proposed, focusing on collaborative activities that promote self-awareness, empathy, impulse control, decision-making, and teamwork